Avaliação do potencial antinociceptivo e mecanismo de ação do 2-[5-triclorometil-5-hidroxi-3-fenil-4,5-dihidro-1hpirazol- 1-il] 4-(4 bromofenil)- 5 metiltiazol (b50) em camundongos - Souza, Alessandra Hübner de (2005)
Pain is a common symptom in the clinical practice. Therefore, novel analgesic drugs, with more favorable pharmacological properties have been searched. Previous studies from our group showed that the systemic administration of the 2-[5-triclorometyl-5-hidroxy-3-phenyl-4,5-dihydro-1H-pyrazole-1-yl]-4-(4-bromophenyl)-5-metyl-thiazole(B50) causes antinociception in the acetic acid writhing test. However, it is not know whether such an antinociceptive action involves central or peripheral mechanisms. In this study we investigated the antinociceptive effect of the intrathecal administration of the new pyrazole derivative 2-[5-triclorometyl-5-hidroxy-3-phenyl-4,5-dihydro-1H-pyrazole-1-yl]-4-(4- bromophenyl)-5-metyl-thiazole (B50) in adult male mice, using the acetic acid writhing induced by acetic acid and hot-plate tests, in order to determine its putative site of action. B50 caused antinociception (200 nmol/ 5 μl, i.t.), 120 minutes after its administration, in the acetic acid writhing assay and 90 minutes after its administration in the hot plate test. Naloxone (8.25 μmol/kg, s.c.) reverted the antinociceptive action of B50 (200 nmol/ 5 μl, i.t.) in the acetic acid writhing assay, suggesting that opioid mechanisms are involved in the antinociception caused by B50. B50 had no effect on spontaneous locomotion or rotarod performance, indicating that the currently reported antinociceptive effect of B50 is not related to unspecific motor effects.